Health is wealth : mass meeting of miners (poster)
1926-02-21 1926 1920s 1 page Industrial Health Education Council "HEALTH IS WEALTH." MASS MEETING OF MINERS and others interested in the Mining Community IN LA SCALA PICTURE HOUSE, HAMILTON, (By kind permission of the Magistrates and the Management.) ON SUNDAY, 21ST FEBY. At 3 o'clock p.m. Dr. WILLIAM DENNESS, Bothwell, Will speak on "Miners' Sicknesses and Diseases." Dr. CHAS. READ, L.D.S., Glasgow, Will speak on "Teeth in Relation to Health, and what X-Rays reveal on Teeth Decay." There will also be shown Two Films, one by the Dental Board on "The Care of the Teeth." and one by the Ministry of Health on "Dr. Wise on Influenza." CHAIRMAN, - - WILLIAM B. SMALL, ESQ. All interested in the Mining Community invited --- including Ladies. QUESIONS AT THE CLOSE. ADMISSION FREE. 200/B/3/2/C693/1/45